Emigration Intentions and Risk Aversion: Causal Evidence from Albania - Michel Beine; Gary Charness; Arnaud Dupuy (Center for Economic Studies and ifo Institute (CESifo), 2021)
Estimating the impact of risk aversion on emigration at the individual level is complicated by selection issues. In this paper, we use original data from Albania on mobility intentions and elicited risk aversion to provide causal estimates on this relationship. Our identification strategy relies on the occurrence of two earthquakes during data collection that unambiguously led to upward shifts in risk aversion as shown in a companion paper (Beine et al., 2021). While OLS estimates fail to capture a (negative) relationship between risk aversion and emigration intention, a Control Function strategy using the two earthquakes as instruments uncovers such a relationship. We argue that our results highlight a new channel through which risk preferences explain the trapped population phenomenon documented in the climate change and migration literature.
Keywords: F22; O15; P16; O57; 330; emigration; risk aversion; earthquakes; trapped population phenomenon